Electronic Medical Records and Cost Efficiency in Hospital Medical-Surgical Units - Michael F. Furukawa; T. S. Raghu; Benjamin B. M. Shao (SAGE Publishing, 2010)
This study examines the impact of electronic medical records (EMRs) on cost efficiency in hospital medical-surgical units. Using panel data on California hospitals from 1998 to 2007, we employed stochastic frontier analysis (SFA) to estimate the relationships between EMR implementation and the cost inefficiency of medical-surgical units. We categorized EMR implementation into three stages based on the level of sophistication. We also examined the effects of specific EMR systems on cost inefficiency. Our SFA models addressed potential bias from unobserved heterogeneity and heteroskedasticity. EMR Stages 1 and 2, nursing documentation, electronic medication administration records, and clinical decision support were associated with significantly higher inefficiency.